â€œThe Effect of Human Resources Quality on Economic Growth of Districts and Cities in that Province of West Kalimantanâ€. - B01109117, Susan Sri Wijayati (Jurnal Pembangunan dan Pemerataan, 2015)
The objective of this study is to investigate the effect of human resource quality on economic growth of districts and cities in the province of west Kalimantan. The data was panel data which had a combination of time series (2008-2012) and cross-point (14 districts or cities in the province of West Kalimatan) published by statistical center departement of West Kalimantan province and subsequently the data was processed by eviews 6.0 program. The results indicated that the life expectancy and literacy rates had a positive relationship and significant effect on economic growth. Mean while percapita real expenses had negative relationship and did not have significant effect on the economic growth of districts and cities in the province of West Kalimantan in the period of 2008-2012. Keywords : life expectancy, literacy rates, per capita real expenses, economic growth.